The Development of Pancasila Student Profile towards the Benefits of Democratic Voice from an Islamic Perspective: Students' View - Yosi Febriani; Maria Montessori; Junaedi Indrawan; Darmansyah Darmansyah; Yovhandra Ockta (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2024)
This study aims to analyze the benefits of the democracy vote project in developing the Pancasila student profile, analyze the factors that affect the democracy vote project and describe students' perceptions of the democracy vote project at SMP Negeri 3 Gunung Talang, Solok Regency. The method used in this study is the Mix Methode of Sequential Exploratory design. The research was conducted on 15 informants and 55 respondents. Data were obtained by interviews, observations, documentation studies and filling out questionnaires. The results of the study show that the democratic voice project contributes to developing a profile of critical reasoning, cooperation and global diversity in students, while the factors that support the implementation of the democratic voice project include school readiness, student enthusiasm and enthusiasm, teacher competence and collaboration between teachers. Meanwhile, the factors that hinder the democratic vote project include a lack of support from students' parents, different teacher abilities and time management facilities and there are still some students who do not focus on participating in the democratic vote project activities. Furthermore, regarding the students' perception of the democratic vote project, it is good. This can be seen from the average percentage of student knowledge indicators about the democracy vote project, which is obtained on average 75.95% which is categorized as good. The indicator of student understanding of the content of the democracy vote project was obtained 86.05% which was categorized as good and the indicator of student assessment of the implementation of the democracy vote project was obtained 81.60% which was categorized as good. The overall achievement level of student perception was obtained with an overall average of 81.20%. So it can be concluded that the students' perception of the democratic vote project at Junior High School of 3 Gunung Talang is good. The implication of this research is that the implementation of the democratic voice project needs to be better organized and managed, and teachers need to improve their abilities through trainings to be more optimal in achieving the target of developing the Pancasila student profile. Students are expected to concentrate more on participating in project learning activities. As well as the need for support from parents and school committees to support the implementation of the vote project demorkasi democracy in schools.